Development of Stroke Fast Track Care Management for Emergency Nurses in Community Hospitals, Phrae Province - ชัยนันท์ กรรณิการ์; แสงด้วง นิพิฐพนธ์; เด็ดขาด เสาวภา (Journal of Phrae Public Health for Development - วารสารสาธารณสุขแพร่เพื่อการพัฒนา, 2023)
This purpose of study was to develop nursing quality management in patients with stroke symptoms at emergency department of Community Hospital in Phrae Province. Using research and development (The Research and Development) as a conceptual framework for development and implementation of clinical practice guidelines for acute stroke patients. The sample consisted of 1) 82 professional nurses who worked at the emergency department. 2) 151 patients with acute ischemic stroke who receive treatment in the emergency department. The instruments used in the study were questionnaires of nurses. Nursing management Record form for Stroke Patients. Its contents validity had been approved by 3 experts and the Index of Item-Objective Congruence were 0.60–1.00 as well as the Cornbrash’s Alpha Coefficient were 0.95. The data were used interferential statistical analysis. The results of this study indicated that 1) There are quality management guidelines that can actually be used for stroke patients for Emergency nurses at emergency department of Community Hospital in Phrae Province. 2) all 82 participated nurses agreed that it was plausible to implement these CNPGs. Most nurses satisfied at highest level (93.90%). 3) The average time of patient transfering was declined from 34.91 minutes to 29.38 minutes. It is recommended that nurse should be trained on health assessment of the neurological, especially signs of acute ischemic stroke. Further study should evaluate the effectiveness of the clinical nursing practice guidelines.